The Bachelor of Science in Hospitality Management Educator’s In the Second District of Albay - Belga-GallaS, Chona (JPAIR Institutional Research, 2025)
This study assesses the competencies of Bachelor of Science in Hospitality Management educators in the Second District of Albay, focusing on their academic profile, professional experience, and proficiency in key competency areas. Specifically, it examines their industry knowledge, pedagogical skills, communication abilities, leadership management, customer service expertise, technology proficiency, research and analytical skills, professionalism and ethics, and mentorship engagement. The research also explores the challenges faced by educators in meeting these competencies and the actions taken to address them. Using a descriptive research design, data was collected through surveys and interviews with educators from various Higher Education Institutions (HEIs) in the district. Findings indicate gaps in research proficiency, technology integration, and industry exposure, which impact the overall effectiveness of teaching in hospitality education. Time constraints, limited professional development opportunities, and lack of institutional support were identified as key challenges. To bridge these gaps, this study proposes a Hospitality Management Educators’ Competency Enhancement Framework, emphasizing continuous training, industry immersion, and institutional reforms. The framework aims to develop a more industry-responsive, student-centered, and globally competitive faculty. The study’s findings serve as a foundation for enhancing hospitality education and ensuring educators are equipped to meet evolving industry demands.
Keywords: Hospitality Management; Educator Competencies; Tourism Education; Professional Development; Albay